L’informalità del capitale: tempi, lavoro e capitalismo delle piattaforme - Cingolani, Patrick (Cambio. Rivista sulle Trasformazioni Sociali, 2021)
The outsourcing movement of the second half of the 20th century had fueled informality on its edges: illegal workers in European construction companies or sweatshops of subcontractors from developing countries with unsanitary buildings and degraded working conditions. Digitization in the 21st century has reconfigured this movement in an original way, shifting work towards the home or towards the sphere of everyday life. The article attempts to explain the ways in which capitalism invades spheres and areas that sometimes remained relatively unspoiled or free: random mobility of the driver or the rider of the platforms; interstitial temporality of the “turkers” or “click workers”, space for staging oneself or for gaming on YouTube; amateur management at Lego. The informality of capital is here the effect of the original process of market colonization of the interstitial time in everyday life.